Analisis Dampak Lingkungan dengan Pendekatan DPSIR Akibat Pola Penggunaan Lahan (Studi Kasus: Kabupaten Bantaeng Sulawesi Selatan) - Maula, Rahmatun; Dewi Fitria Marlisa; Iqbal Kamaruddin; Qanitatul Isra Qamal (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Bantaeng Regency is experiencing increasing environmental pressure driven by population growth and land-use changes that reduce natural infiltration capacity. These conditions heighten flood potential and increase infrastructure vulnerability, particularly in urban and lowland areas. This study aims to analyze the environmental conditions of Bantaeng Regency using the DPSIR (Driving Force–Pressure–State–Impact–Response) framework. The DPSIR method was applied through the analysis of population growth, land-use patterns, rainfall intensity, infiltration areas, and spatial flood vulnerability. The results show that population continues to increase, infiltration areas cover approximately 15,421.96 hectares, and rainfall peaks in February and reaches its lowest level in October at (1,094.70 and 2.5) mm, respectively. Areas categorized as having low, medium, and high flood vulnerability cover (1,6425; 5,564; and 17,108) hectares, particularly in regions experiencing intensive and urban land conversion. In addition, road infrastructure is exposed to low, medium, and high flood vulnerability along (4.97; 9.35; and 52.31) km, while residential areas and public facilities also show increasing risks of inundation-related damage. These findings highlight the need for adaptive and sustainable environmental management strategies, including improved drainage capacity, construction of retention ponds, expansion of infiltration zones, and strengthening of Green Open Space.